Patterns of cerebral amyloid angiopathy define histopathological phenotypes in Alzheimer's disease. Issue 2 (February 2014) - Allen, N.; Robinson, A. C.; Snowden, J.; Davidson, Y. S.; Mann, D. M. A.
<x xml:space="preserve">Abstract</x> Aims Pathological heterogeneity of Aβ deposition in senile plaques (SP) and cerebral amyloid angiopathy (CAA) in Alzheimer's disease (AD) has been long noted. The aim of this study was to classify cases of AD according to their pattern of Aβ deposition, and to seek factors which might predict, or predispose towards, this heterogeneity. Methods The form, distribution and severity of Aβ deposition (as SP and/or CAA) was assessed semiquantitatively in immunostained sections of frontal, temporal and occipital cortex from 134 pathologically confirmed cases of AD. Results Four patterns of Aβ deposition were defined. Type 1 describes cases predominantly with SP, with or without CAA within leptomeningeal vessels alone. Type 2 describes cases where, along with many SP, CAA is present in both leptomeningeal and deeper penetrating arteries. Type 3 describes cases where capillary CAA is present along with SP and arterial CAA. Type 4 describes a predominantly vascular phenotype, where Aβ deposition is much more prevalent in and around blood vessels, than as SP. As would be anticipated from the group definitions, there were significant differences in the distribution and degree of CAA across the phenotype groups, although Aβ deposition as SP did not vary. There were no significant differences between phenotype groups with regard to age of onset, age at death, disease duration and brain weight, or disease presentation. Women were over‐represented in the type 1 phenotype and men in type 2. Genetically, type 3 (capillary subtype) cases were strongly associated with possession of the APOE ε4 allele. Conclusions This study offers an alternative method of pathologically classifying cases of AD. Further studies may derive additional genetic, environmental or clinical factors which associate with, or may be responsible for, these varying pathological presentations of AD.